Deoxynivalenol Induces Inflammation in the Small Intestine of Weaned Rabbits by Activating Mitogen-Activated Protein Kinase Signaling - Wang, Pengwei; Huang, Libo; Yang, Wanying; Liu, Quancheng; Li, Fuchang; Wang, Chunyang (Frontiers in Veterinary Science, 2021)
Deoxynivalenol (DON) can activate related signaling pathways and induce gastrointestinal disorders. Based on the results of previous studies, this study tried to explore the relationship between DON-induced intestinal inflammation of weaned rabbits and the ERK-p38 signaling pathway. Forty-five weaned rabbits were divided into three treatments: control, LD and HD group. All rabbits were treated with diet containing a same nutrient content, but animals in the LD and HD groups were additionally administered DON via drinking water at 0.5 and 1.5 mg/kg b.w./d, respectively. The protocol consisted of a total feeding period of 31 days, including a pre-feeding period of 7 days. Western blotting, qRT-PCR, and immunohistochemistry were applied for analysis the expression of protein and mRNA of extracellular signal-regulated kinase (ERK), p38, double-stranded RNA-activated protein kinase (PKR), and hematopoietic cell kinase (Hck) in the duodenum, jejunum, and ileum of rabbits, as well as the distribution of positive reactants. The results proved that DON intake could enhance the levels of inflammatory factors in serum and damage the intestinal structure barrier of rabbits. Meanwhile, DON addition can stimulate the protein and mRNA expression for ERK, p38, PKR, and Hck in the intestine of rabbits, especially in the duodenum, as well as expand the distribution of positive reactants, in a dose-dependent manner.